BASAL CELL CARCINOMA EXCISION INTRAOPERATIVE FROZEN SECTION FOR TUMOUR CLEARANCE AND RECONSTRUCTIVE SURGERY - Tahir, Moizza; Uzma Bashir; Aisha Akhtar; Sidiqua Javaid; Zainab Ansari; Sameen Ansari (Journal of Ayub Medical College Abbottabad, 2024)
Background: Basal cell carcinoma (BCC) is the most common skin cancer. The majority of BCC are in Europe, US and Australia. Annual incidence in US is 2 million per year with an increase of 0.87% 1. Sun exposure to face, ears, neck, back, shoulders and hands are attributable factors Objective was to report intraoperative frozen section clearance rate of tumour margins and depth for excised basal cell carcinoma in a tertiary care center and find the frequency of tumour involved surgical margins concerning the anatomical site, size, and surgical technique. Method; It was a prospective open-label interventional study conducted at the Dermatology department of tertiary care hospital Rawalpindi (Pakistan) in liaison with the histopathology department from January 2023 to April 2024. Patients aged from 45–80 years, with a clinical diagnosis of basal cell carcinoma, having a size of 10–35 mm located on the face were included as per inclusion/ exclusion criteria. A surgical excision was performed under local anaesthesia at the dermatology department. An intraoperative frozen section for tumour margins and depth was taken from a histopathologist. The surgical defect was reconstructed on the same day after the negative report. p-value of <0.05 was considered significant for margin involvement, surgical technique, and anatomical site. Results; A Total of 36 patients of BCC were enrolled. There were 12 (33.3%) males and 24 (66.6%) females. The size of BCC ranged from 10–35 mm mean of 25 mm ±SD 0.63. Tumour-free margins and depth were attained in 77.77% of cases. Tumour excision with a frozen section concerning surgical technique had a chi-square p-value ≤0.51, for anatomical site chi-square p-value ≤0.24, and for size was p-value ≤0.84. Conclusion: Intraoperative frozen section for basal cell carcinoma is a reliable technique for complete tumour excision in our center with 77.7% margin clearance. This technique is resource-intensive and time-consuming. Patients achieve complete excision and better aesthetic outcomes. Patients following surgical excision of basal cell carcinoma on the face with intraoperative frozen section are benefited through preservation of form and function. The intraoperative frozen section is available in tertiary care hospitals in Pakistan. It is resource-intensive for patients living in remote areas. Intraoperative frozen section is recommended for patients where tumour is located at high-risk sites and requires complex reconstruction after tumour excision. Patients should be educated for follow-up visits in case of induration, morphological changes, or new developments in scar which may require re-excision